PENGARUH APLIKASI KOMPOS GRANUL ELA SAGU DIPERKAYA PUPUK PONSKA TERHADAP SIFAT FISIK TANAH DAN HASIL JAGUNG MANIS DI INCEPTISOL - Maimuna La Habi (BIOPENDIX, 2015)
Background: the sago flour is the main result of the sago palm, while the byproduct or waste sago generally used for animal feed, compost in mushroom growing media, or as raw material for the plywood industry. Sago waste by the people of Maluku called ela sago can also play a role in improving soil fertility in this case improve the physical, chemical and biological soil after going through stages of processing into granules and granule enriched compost. Methods: The study design used was a randomized block design with three replications. The treatment consists of: without fertilizer (KGES1), compost granule 8 t ha-1 (KGES2), inorganic fertilizers (Urea, SP-36 and KCl) recommended dosage (KGES3), inorganic fertilizer + compost granule 8 t ha-1 (KGES4), Â½ x doses of inorganic fertilizer + compost granule (8 t ha-1) (KGES5), 2 doses of inorganic fertilizer + compost granule 8 t ha-1 (KGES6), Â½ x doses of inorganic fertilizer + compost granule 12 t ha -1 (KGES7) and 2 doses of inorganic fertilizer compost + 4 t ha-1 (KGES8). Results: Compost granules ela sago and inorganic fertilizer significantly affect the physical properties of soil that is heavy volume of land (0.80 g cm-3), a specific gravity of soil particle (2:30 g cm-3), soil porosity (7.77%), drainage pore fast (23:54%), slow drainage pores (8.83%), pore water is available (11.62%), and pore water is not available (11:31). While plant growth (plant height) and dry seed corn grain yield respectively by 249.17 cm and 7.85 tonnes ha-1. A combination of compost and inorganic fertilizer granule able to increase the yield of 30-47% compared with inorganic fertilizer or compost granule alone. Excessive inorganic fertilizer application did not show the result of increased dry seeds shelled corn is real. Based on these results, a reduction of half a dose of inorganic fertilizer combined with granulated compost 12 t ha-1 yield of dry shelled corn grain yield highest (7.79 t ha-1) or increase the yield of 32% of inorganic fertilizer application. Conclusion: Compost granules ela sago and inorganic fertilizer significantly affect soil physical properties ie soil bulk density (0.80 g cm-3), soil particle density (2:30 g cm-3), soil porosity (7.77%), soil macropore (23:54%), mesopore (8.83%), and micropore (11.62%). While plant growth (plant height) and dry seed corn grain yield respectively by 249.17 cm and 7.79 tonnes ha-1. A combination of compost and inorganic fertilizer granule able to increase the yield of 30-47% compared with inorganic fertilizer or compost granule alone. Excessive inorganic fertilizer application did not show the result of increased dry seeds shelled corn is real.